The Effect of Enterprise Risk Management Practice on SME Performance - Yakob, Sajiah; -Syah, Hafizuddin, B.A.M.; Yakob, Rubayah; Raziff, Nur Aufa Muhammad (The South East Asian Journal of Management, 2019)
Research Aims - This study aims to identify the effect of Enterprise Risk Management (ERM) on Small and Medium Enterprise (SME) performance. Design/methodology/approach - This study employed a multiple regression analysis. SME performance was treated as dependent variable, whereas ERM was the independent variable. Research Findings - Multiple regression analysis indicated that ERM has a significant effect to- wards firm performance. However, only one of the ERM elements namely objective determination has a significant effectt on SME performance. Theoretical Contribution/Originality - This study contributes to the body of knowledge from the standpoint of ERM by testing the effect of each element of ERM described under the Committee of Sponsoring Organizations of the Treadway Commissions (COSO) towards firm performance. Per- haps, each element of the ERM might has different effect towards an organization. Thus, Resource Based View (RBV) Theory was supported which hold that the organisational resources are the main factor to influence the organisational performance. Managerial Implication in the South East Asian context - ERM conducted in SMEs are expected to be able to develop strategies in minimising the risks that may or may not be faced by SME firms. In fact, an effective risk management can assist SME managers and owners in achieving their de- fined business objectives. Thus, risk management enhances the firm’s value, maximise profitability, and consequently improve SME performance. Research limitation & implications - This study has improved the measurement of ERM practices among SMEs and identified ERM elements that affect SME performance in particular.